The Benefits of Tamarillo Fruit for Increasing Hemoglobin Levels in Pregnant Women in the First Trimester as Local Wisdom in 2025 - Willhelmina Wahara; Emelia Apriani br. Tampubolon; Dwi Ris Hasanah S; Dosma Rointan Sipahutar; Elisabeth Fransiska Sitorus (PT Inovasi Pratama Internasional, 2025)
Anemia in pregnant women is a health problem that can increase the risk of complications during pregnancy and childbirth, as well as impaired fetal development. One non-pharmacological method to increase hemoglobin (Hb) levels is to consume natural ingredients rich in iron and vitamin C, such as tamarillo fruit. Objective: This study aims to determine the benefits of consuming tamarillo fruit on increasing hemoglobin levels in pregnant women in the second trimester at the Hanna Kasih Clinic in Medan in 2025. Methods: This study used a pre-experimental design with a one-group pretest-posttest approach . The study sample consisted of 15 pregnant women in their second trimester who met the inclusion criteria. Respondents were given 200 ml of tamarillo juice per day for 30 days. Hb levels were measured before and after the intervention using a digital hemoglobinometer. Data were analyzed using a paired t-test to determine the difference in mean Hb levels before and after treatment. Results: The results of the Community Activity Implementation showed an increase in Hb levels from 10.2 g/dl to 11-11.8 g/dl after administering tamarillo juice. Statistical tests showed a p -value <0.05, which means there was a significant difference between Hb levels before and after the intervention. Conclusion: Consuming tamarillo juice significantly increases hemoglobin levels in pregnant women in the second trimester. The iron, vitamin C, and antioxidants in tamarillo play a role in aiding iron absorption and hemoglobin formation. Tamarillo fruit can be a natural alternative to prevent anemia in pregnant women.